Specialized eRpL22 paralogue-specific ribosomes regulate specific mRNA translation in spermatogenesis in Drosophila melanogaster. - Mageeney, C.M.; Ware, V.C. (Molecular Biology of the Cell, 2019)
The functional significance of ribosome heterogeneity in development and differentiation is relatively unexplored. We present the first in vivo evidence of ribosome heterogeneity playing a role in specific mRNA translation in a multicellular eukaryote. Eukaryotic-specific ribosomal protein paralogues eRpL22 and eRpL22-like are essential in development and required for sperm maturation and fertility in Drosophila. eRpL22 and eRpL22-like roles in spermatogenesis are not completely interchangeable. Flies depleted of eRpL22 and rescued by eRpL22-like overexpression have reduced fertility, confirming that eRpL22-like cannot substitute fully for eRpL22 function, and that paralogues have functionally distinct roles, not yet defined. We investigated the hypothesis that specific RNAs differentially associate with eRpL22 or eRpL22-like ribosomes, thereby establishing distinct ribosomal roles. RNA-seq identified 12,051 transcripts (mRNAs/noncoding RNAs) with 50% being enriched on specific polysome types. Analysis of ?10% of the most abundant mRNAs suggests ribosome specialization for translating groups of mRNAs expressed at specific stages of spermatogenesis. Further, we show enrichment of "model" eRpL22-like polysome-associated testis mRNAs can occur outside the germline within S2 cells transfected with eRpL22-like, indicating that germline-specific factors are not required for selective translation. This study reveals specialized roles in translation for eRpL22 and eRpL22-like ribosomes in germline differentiation.